Pengaruh Rasio Likuiditas dan Rasio Aktivitas Terhadap Kinerja Keuangan Perusahaan Wadah dan Kemasan Di BEI Tahun 2020-2022 - Dharajaty, Hilmi; Syahyuni, Dedy (ProBisnis : Jurnal Manajemen, 2024)
The success of the company is a reflection of the company's successful financial performance. A financial performance can be seen from the evaluation of the company's financial statements. The purpose of this paper is to determine the effect of the liquidity ratio and the amount of activity ratio on financial performance in container and packaging companies listed on the Indonesia Stock Exchange (IDX) in 2020-2022. The type of research used is statistical quantitative method. Determination of the sample in this paper uses purposive sampling method and a total of ten container and packaging companies are obtained as samples. The technique of data collection uses documentation and online research methods. In analyzing the data the author runs the classical assumption test and multiple linear regression using the help of SPSS 25 software. There are two independent variables used in this paper, namely the liquidity ratio (X1) and the activity ratio (X2), then the dependent variable is financial performance (Y). From the partial test results, it shows that there is no significant effect of the liquidity ratio on financial performance, while for the activity ratio there is a significant effect on the company's financial performance. For the t test, the liquidity ratio and activity ratio are stated to have a joint effect on the financial performance of container and packaging companies.